Challenges facing the development of new nuclear capacity in South Africa - Makhubela, Thomas (Department of Electrical Engineering, 2024)
South Africa currently (2022) hosts two nuclear reactor facilities, the electricity generating Koeberg nuclear power plant, and the SAFARI - 1 reactor, which is used for medical isotope production, research, and development. With the nationwide problems of loadshedding due to a lack of operational capacity, resulting in economic decline, and the climate concerns associated with fossil fuels, the addition of nuclear capacity is an appealing concept. This dissertation details several of the challenges associated with the development of new nuclear power plants (NPPs) in South Africa, from the availability of nuclear fuel and technical expertise to environmental, political, and economic issues. These challenges were explored in both national and international spheres, drawing on case studies from around the world. The long-term operation of the existing nuclear capacity was considered, alongside the viability of spent nuclear fuel re-processing in the South African context as a strategy for waste management and generation of revenue. Ultimately, political factors, and public participation and acceptance were identified as the primary challenges that have delayed the deployment of NPPs, which need to be addressed by the government when developing a rigid national nuclear energy policy to sustain South Africa's economy both for current and future generations.